New Opportunities in Dexmedetomidine Acoustic Anesthesia - Khudoyberdiyeva Gulrukh Sobirovna; Khudoyberdieva Gulrukh Sobirjonovna (Genius Journals, 2024)
The problem of anesthesia for delivery in the abdominal cavity has long been solved. At the same time, spinal (SA) and epidural anesthesia (EA), as well as general multicomponent anesthesia (GA) with mechanical ventilation are used as anesthetic assistants [1]. Each of these methods has its advantages and disadvantages, indications and contraindications. In modern obstetrics, the choice of anesthesia for caesarean section is of particular importance, as it should contribute to adequate protection of the pregnant woman from surgical stress and create optimal conditions for the adaptation of the fetus in the perioperative and neonatal period.
Keywords: perioperative; with; ventilation; anesthesia